Relative deprivation and depressive symptoms among Chinese migrant children: The impacts of self-esteem and belief in a just world - Meng Xiong; Meng Xiong; Zhiqin Hu (Frontiers Media S.A., 2022)
BackgroundStudies have shown that relative deprivation is a risk factor for depressive symptoms, but the underlying mechanisms are not yet clarified. Thus, this study formulated a moderated mediation model to investigate the mediating role of self-esteem and the moderating role of belief in a just world between relative deprivation and depressive symptoms among rural-to-urban migrant children.MethodsA sample of 1,076 Chinese migrant children (Mage = 12.25 years, SD = 1.66) completed measurements of relative deprivation, self-esteem, belief in a just world, and depressive symptoms. Furthermore, the mediating mechanism and moderating effect of the study were explored with the SPSS PROCESS macro (Models 4 and 7).ResultsThe results showed a significant positive association between relative deprivation and depressive symptoms, with self-esteem partially mediating this association. Moreover, belief in a just world moderated the association between relative deprivation and self-esteem. Namely, the indirect effect of self-esteem was moderated by belief in a just world. Specifically, the mediating effect was stronger for migrant children with higher levels of belief in a just world.ConclusionThese findings broaden our knowledge of how and when relative deprivation influences depressive symptoms among migrant children. Therefore, appropriate measures should be taken to prevent and manage migrant children' depression and provide them with corresponding guidance. Some measures could be taken by schools and educators to help migrant children with high relative deprivation in improving their self-esteem and belief in a just world, such as self-reference tasks and psychological intervention programs.